Editorial commentary: Cutting the Gordian knot of right‐sided prosthetic valve thrombosis. Issue 4 (7th January 2022) - Poschner, Thomas; Mach, Markus; Andreas, Martin; Russo, Marco
Abstract: With limited data available for the tricuspid valve, there are no stringent recommendations in the current guidelines (ESC 2021). Valve replacement for the right‐sided heart is inherently problematic and bears the potential for complications — including prosthetic valve thrombosis (PVT). The purpose of this editorial is to review the key features of this clinical scenario and to outline the essential aspects for optimized patient management and improved outcome. Depending on the clinical presentation of PVT, either immediate surgery, thrombolysis, or anticoagulation may be considered — with the sole intensification of anticoagulation likely being the most inferior. Given the high risk of re‐thrombosis, a dedicated follow‐up program is essential to identify complications early and offer adequate treatment.